Covered call writing’s effect on risk and returns, analysis on Finnish stock market companies - Oittinen, Toni (My University, 2024)
This study investigates the impact of the covered call strategy on risk and returns, focusing on individual stocks within the Finnish stock market. Given the limited research on covered calls in smaller markets, this analysis fills a gap by examining the effectiveness of this strategy during the volatile period of 2020 to 2021. The research employs historical data on option prices and stock returns from ten Finnish companies. The primary objective is to determine whether covered calls can enhance investor returns and how stock performance variations influence these returns. Results indicate that while covered calls generally increase returns compared to a traditional buy and hold strategy, their effectiveness heavily depends on market dynamics. Specifically, the strategy performs best in sideways or weak markets where stock gains are moderate. Additionally, the study confirms that covered calls significantly reduce investment risk, as evidenced by the decreased volatility across all companies examined. The Sharpe ratio analysis suggests an improvement in risk-adjusted returns for most companies when employing this strategy.

Tämä tutkimus tarkastelee taatun osto-optio strategian vaikutusta riskiin ja tuottoihin, keskittyen yksittäisiin osakkeisiin Suomen osakemarkkinoilla. Taatuista osto-optioista on tehty vain vähän tutkimusta pienemmillä markkinoilla, joten tämä analyysi täyttää aukon tutkimalla strategian tehokkuutta volatiilien vuosien 2020–2021 aikana. Tutkimuksessa käytetään historiallista dataa kymmenen Suomalaisen yrityksen optiohinnoista ja osaketuotoista. Ensisijainen tavoite on selvittää, voivatko taatut osto-optiot parantaa sijoittajan tuottoja ja miten osakkeiden tuottojen vaihtelut vaikuttavat strategian lisätuottoihin. Tulokset osoittavat, että vaikka taatut osto-optiot yleensä lisäävät tuottoja verrattuna perinteiseen osta ja pidä-strategiaan, niiden tehokkuus riippuu suuresti markkinaolosuhteista. Erityisesti strategia toimii parhaiten lisätuottojen valossa sivuttain kulkevilla tai heikoilla markkinoilla. Lisäksi tutkimus vahvistaa, että taatut osto-optiot vähentävät merkittävästi sijoitusriskiä, kuten kaikkien tutkittujen yritysten volatiliteetin lasku osoittaa. Lisäksi riskikorjattujen tulosten analyysi viittaa riskikorjattujen tuottojen paranemiseen useimmilla yrityksillä, kun käytetään kyseistä taattujen optioiden strategiaa.
Keywords: Covered call, Options, Risk, Return, taattu osto-optio, optiot, riski, tuotto